Prosedur Pengembangan Kompetensi Untuk Meningkatkan Kinerja Pegawai Di PPSDM Migas Cepu - Ammad Beny Prasetya; Rio Candra Pratama (widya balina, 2025)
. Industrial Internship (KPI) is a form of student learning that emphasizes the direct application of knowledge in the workplace. This study aims to describe the procedures for employee competency development at PPSDM Migas Cepu as an effort to improve organizational performance. The research employed a descriptive qualitative method with data collected through interviews, observations, and document analysis. The findings indicate that competency development at PPSDM Migas is carried out systematically through three main stages: identifying and planning development needs, implementing training programs, and evaluating outcomes using the CIPP, Kirkpatrick, and Kirkpatrick-Philips models. Training activities include courses, workshops, on-the-job training, and certification programs. Evaluations are conducted periodically to ensure program effectiveness and alignment with organizational needs. These findings highlight the importance of human resource management and supervisor involvement in maximizing competency development outcomes. The results of this internship can serve as a reference for designing training programs in similar institutions.